Does Size Matter in the Hedge Fund Industry? - TEO, Melvyn (Institutional Knowledge at Singapore Management University, 2009)
We document a negative and convex relationship between hedge fund size and future riskadjusted returns. Small hedge funds outperform large hedge funds by 2.75 percent per year after adjusting for risk. This over performance cannot be explained by fund age, leverage, serial correlation, backfill bias, or incubation bias. The capacity constraints are not confined to the smallest funds, and manifest across various investment styles and regions. In particular, they are strongest for funds managed by multiple principals that trade small, illiquid securities, suggesting that the observed diseconomies can be traced to price impact and hierarchy costs (Stein, 2002). Interestingly, these capacity constraints facing individual hedge funds do not extend to funds of hedge funds.